COMPARISON OF PHOTOTHERAPY AND PROBIOTIC WITH PHOTOTHERAPY ALONE IN THE TREATMENT OF NEONATAL JAUNDICE (The Research of Medical Science Review, 2025)
Background: Unconjugated bilirubin elevation causes neonatal jaundice which affects more than 60% of term newborns along with 80% of preterm babies. The absence of proper treatment allows kernicterus to develop alongside neurological damage. Illustrating new evidence indicates that probiotics act to boost bilirubin clearance along with their ability to reduce recovery duration. Objectives: The study evaluates whether combining phototherapy treatment with probiotics produces better results than phototherapy alone for serum bilirubin reduction when treating jaundice in newborns. Study design: A Randomized Control Trial Place and duration of study: From October 2023 to March 2024 Paediatrics Department, Sandeman Provincial Hospital / Bolan Medical College/ Hospital Quetta. Balochistan. Methods: This Randomized Control Trial Conducted in the Sandeman Provincial Hospital / Bolan Medical College/ Hospital Quetta. Balochistan from October 2023 to March 2024. The study included 150 healthy newborns with natural jaundice who were separated into two distinct groups. The trial split participants into two groups: group A containing 50 neonates who received phototherapy and probiotics and group B including 50 neonates who received phototherapy alone. Medical staff measured bilirubin levels in the patients' blood before the study and then again, every day for 24 hours. The study analyzed data through SPSS version 24.0 and treated any significance below 0.05 as statistically meaningful. Results: 150 neonates whose gender distribution consisted of 55 males and 95 females. The enrolled neonates had an average age of 4.3 ± 1.2 days at registration. Group A received phototherapy treatment for 36.4 ± 6.2 hours while Group B required 48.7 ± 7.1 hours of phototherapy according to a p < 0.001 analysis. Newborns in Group A experienced substantially better bilirubin reduction (5.2 ± 1.1 mg/dL) at 24 hours compared to Group B (3.7 ± 0.9 mg/dL) with a statistical significance of < 0.01. All babies in both treatment groups experienced no side effects during their hospital stay and left with stable health. Conclusion: Neonates with jaundice experience better bilirubin reduction coupled with shorter phototherapy sessions when given probiotics alongside phototherapy. Neonatal outcomes show potential improvements when practitioners use this method which combines both safety and low costs.